Improvement Science: conceptual and theoretical foundations for its application to healthcare quality improvement - Margareth Crisóstomo Portela; Sheyla Maria Lemos Lima; Mônica Martins; Claudia Travassos
Abstract: The development and study of healthcare quality improvement interventions have been reshaped, moving from more intuitive approaches, dominated by biomedical vision and premised on easy transferability, to gradually acknowledge the need for more planning and systematization, with greater incorporation of the social sciences and enhancement of the role of context. Improvement Science has been established, with a conceptual and methodological framework for such studies. Considering the incipient of the debate and scientific production on Improvement Science in Brazil, this article aims to expound its principal conceptual and theoretical fundamentals, focusing on three central themes: the linkage of different disciplines; recognition of the role of context; and the theoretical basis for the design, implementation, and evaluation of interventions.